2018
DOI: 10.18203/2320-1770.ijrcog20180171
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anaemia and its effects on neonatal anthropometric parameters in patients attending a tertiary care institute of Solan, Himachal Pradesh, India

Abstract: Background: Anaemia during pregnancy is a significant concern in India. The consequences of iron deficiency anaemia during pregnancy are often serious and long lasting for both the mother and the foetus. Haematocrit measurement is an acceptable and recommended method for anaemia determination especially in situations where limited resources are available, and the technical support is poor. There is a rough conversion factor of 3 which converts the HCT value to approximate haemoglobin level. Present study desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This indicates the two methods are Identical within inherent imprecision of both methods. A study in India showed that there was a correlation between calculated hemoglobin and observed hemoglobin (r = 0.94) but acceptability has failed based on the limit of agreement of the Bland and Altman method [22]. This might be due to the fact that the study only involved women on 3 rd trimester and the repeatability also gets worse as the severity of anemia increases.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the two methods are Identical within inherent imprecision of both methods. A study in India showed that there was a correlation between calculated hemoglobin and observed hemoglobin (r = 0.94) but acceptability has failed based on the limit of agreement of the Bland and Altman method [22]. This might be due to the fact that the study only involved women on 3 rd trimester and the repeatability also gets worse as the severity of anemia increases.…”
Section: Discussionmentioning
confidence: 99%
“…LBW is associated with poor health and nutritional outcomes later in life, such as poor growth and development, as well as increased morbidity and mortality in children [10]. Furthermore, severe iron-deficiency anemia has been associated with preterm births [11][12], poor anthropometric measures [13,14], fetal neural development [15], birth asphyxia [16], and increased maternal mortality [17]. Although studies on the impact of anemia during lactation are scarce, available evidence suggests a possible association of anemia among lactating women.…”
Section: Introductionmentioning
confidence: 99%